Outcomes for HIV-associated diffuse large B-cell lymphoma in the modern combined antiretroviral therapy era. (28th November 2017) - Besson, Caroline; Lancar, Remi; Prevot, Sophie; Algarte-Genin, Michele; Delobel, Pierre; Bonnet, Fabrice; Meyohas, Marie-Caroline; Partisani, Marialuisa; Oberic, Lucie; Gabarre, Jean; Goujard, Cécile; Boue, François; et al.
Abstract : Objective: Non-Hodgkin's lymphoma (NHL) remains among the most frequent malignancies in persons living with HIV (PLWHIV). Survival among patients with HIV-associated diffuse large B-cell lymphoma (DLBCL), the most frequent NHL subtype, has improved markedly in recent years. We aimed to analyze characteristics and outcomes of DLBCL in HIV-infected patients in the era of modern combined antiretroviral therapy (cART). Design: PLWHIV with lymphoma were prospectively enrolled in the French ANRS-CO16 Lymphovir cohort between 2008 and 2015. We compared the patients treated with R-CHOP) (rituximab, cyclophosphamide, daunorubicin, vin-cristine, prednisolone) with HIV-negative DLBCL patients enrolled simultaneously in the R-CHOP arms of Lymphoma Study Association trials. Results: Among 110 PLWHIV with NHL, 52 (47%) had systemic DLBCL. These 52 cases had frequent extranodal disease (81%), poor performance status (35%) and advanced age-adjusted international prognostic index (aaIPI) (58%), and were mainly treated with R-CHOP ( n = 44, 85%). Their median CD4 + T-cell count was 233 cells/μl, and 79% of patients were on cART. The 2-year overall and progression-free survival rates were both 75% (95% confidence interval: 64%, 88%). Factors associated with progression or death in univariate analysis were poor performance status [hazard ratio: 3.3 (1.2, 8.9)], more than one extranodal site [hazard ratio: 3.4 (1.1, 10.5)] and an advanced aaIPI [hazard ratio: 3.7 (1.0, 13.1)]. Progression-free survival after R-CHOP therapy did not differ from that of the HIV-negative counterparts ( P = 0.11). Conclusion: In the recent cART era, despite frequent high-risk features, the 2-year overall survival of HIV-DLBCL patients reaches 75%. Outcomes after R-CHOP therapy are similar to those of HIV-negative patients with similar aaIPI. Abstract : Supplemental Digital Content is available in the text